Study on the challenges affecting the legal process for child victims in the criminal justice system in Sri Lanka - Wijesiri, U. K. R. S. P.; Abykoon, A. M. S. J.; Dunuwila, D. H. D. C. (International Conference on Child Protection 2025, University of Kelaniya, Sri Lanka., 2025)
Background: Children are considered the future of a country, and it is a general acceptance that it is the responsibility of a country to ensure the best interest of its children. A child requires adult assistance to maintain their personal life, and a child is defined as someone under the age of 18 according to the United Nations Convention on the Rights of the Child, 1989. Although this age limit varies with various laws in Sri Lanka, actions are carried out based on common acceptance. The process of children becoming victims and their subsequent victimization has become a major challenge to prevent and control. The main research problem of this study was to identify the challenges affecting the legal process in the criminal justice system for child victims in Sri Lanka. Method: Information is being gathered by studying ten ongoing child abuse cases and through conducting interviews with 25 officials involved in the child justice process, while both primary and secondary sources are utilized to gather qualitative and quantitative data. Results: Challenges such as delays in court proceedings, errors in filing cases, delays in sentencing the accused, re-victimization of children during the hearing, non-priority of recording of video evidence or taking evidence from online, failure to updated laws and failure to recognize the relevant legal provisions in prosecuting, neglecting the psychological assessment concerns of the child victims and absence of child-friendly court proceedings and environment were identified here. Furthermore, critical issues have arisen concerning the protection, welfare, education, and vocational training of children, who are in conflict with the law and placed in probation or detention homes, as these matters are not being implemented in a transparent and systematic manner. Conclusion: The study revealed that there is lack of the commitment, trust, consensus, cooperation and coordination among the institutions involved in child related matters and if these factors are properly implemented it would lead to greater effectiveness. Regulating media handling of children and child abuse cases is crucial, and the disclosure of identities and media reporting presents significant challenges. Given the general public's minimal understanding and awareness of child justice processes and legal backgrounds, addressing these challenges with swift solutions has become an urgent necessity.
Keywords: Child rights; child-friendly justice; child video evidence; child-sensitive justice; child victims